(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This paper deals with a brief linguistic analysis of non-self-authored quotations . In non self-authored quotations lexical devices are introduced into the author’s speech in the process of narration about a certain event or various things and by their content belong not to one author, but to the same one. time it has the possibility to belong both to the author and to the character acting within the speech activity. The subject of speech, intended to be portrayed by the author, is expressed through words expressing the subjective views and perceptions of the character. Such words are impressive, stylistically colorful, convey the character’s speech behavior and unique style of expressing thoughts. In such cases, the thoughts that the author intended to express are reflected not from his language, but from another point of view, naturally through other words .